Adverse effects in the female external genitalia of patients with acne vulgaris treated with isotretinoin (Research, Society and Development, 2022)
Adverse effects on the external genitalia have been reported and are likely to be underreported in patients receiving isotretinoin. The aim of this study was to evaluate adverse effects on the female external genitalia in patients with acne vulgaris treated with isotretinoin. This is an analytical cross-sectional design, developed in a university hospital in northeastern Brazil. The study population comprised patients undergoing follow-up treatment for acne with isotretinoin. Sampling was non-probabilistic, of the convenience type, and consisted of 10 participants. Socioeconomic variables, background, isotretinoin treatment data, and adverse effects on female external genitalia were collected. Univariate and bivariate statistics were calculated. Adverse effects on the external genitalia were presented by 40.0% of the women, with a minimum of three and a maximum of five complaints per participant. The most prevalent adverse effects were dyspareunia (40.0%), vaginal dryness (40.0%) and vulvovaginal burning (40.0%), occurring concomitantly. Most patients who underwent waxing on the external genitalia had adverse effects (75.0%). The mean number of platelets was significantly lower in women with adverse effects on the external genitalia (p=0.005). Women with acne grade III had a higher prevalence of adverse effects on the female external genitalia (75.0%). The mean time of use of isotretinoin was 7.5 months, with a mean daily dose of 0.5 mg/kg/day. Adverse effects on the female external genitalia resulting from the use of isotretinoin for the treatment of acne vulgaris appear mainly in the form of mucocutaneous alterations, but not in isolation.